FC006: Sex Differences in the Recognition, Monitoring and Management of Chronic Kidney Disease in Health Care. (3rd May 2022) - Swartling, Oskar; Yang, Yuanhang; M. Clase, Catherine; Fu, Edouard; Hecking, Manfred; Hödlmoser, Sebastian; Trolle Lagerros, Ylva; Evans, Marie; Jesus Carrero, Juan
Abstract: BACKGROUND AND AIMS: Sex-specific differences exist in the population prevalence of chronic kidney disease (CKD), progression rates and health outcomes. Recognition, diagnosis and monitoring are central processes in the management of patients with CKD, but it is unknown whether these processes differ between men and women. METHOD: This is an observational cohort study of all adult individuals ( n = 227 847) with at least one eGFR (from serum creatinine) <60 mL/min/1.73 m 2 during outpatient routine care in Stockholm, Sweden, 2009–2017. Through logistic regression, we evaluated differences by sex in carrying an ICD-10 code for CKD and provision of recommended medications (renin–angiotensin system inhibitors [RASi] and statins) at inclusion. Through Cox regression, we evaluated potential sex differences in receiving a CKD diagnosis, referral to nephrology care and performance of laboratory monitoring (creatinine and albuminuria) in the next 18 months from inclusion. We also explored time-trends, comparing the above-mentioned nephrology care indicators among 70–80 000 unique eligible individuals per calendar year (in total 695 632 observations), thus allowing participants to contribute to different calendar year-cohorts. RESULTS: We identified more women (55%) than men (45%) with probable CKD (eGFR < 60 mL/min/1.73 m 2 ). Women were generally older than men (median 77 versus 74 years), but eGFR was similar between sexes (51 mL/min/1.73 m 2 ). More men than women had diabetes or myocardial infarction, but there was similar prevalence of hypertension. At inclusion and compared with men, women had lower risk of carrying an ICD-10 code for CKD (odds ratio [OR]: 0.47, 95% CI: 0.45–0.49) and were less likely to receive RASi (OR: 0.55; 0.50–0.61, among patient with albuminuria A3) or statins (OR: 0.64; 0.63–0.66, among patients ≥ 50 years), despite the presence of clear indications. In subsequent time-to-event analyses, women were less likely to receive a CKD diagnosis (hazard ratio [HR]: 0.43; 0.42–0.45) and visit a nephrologist (HR: 0.46; 0.43–0.48) regardless of CKD severity, presence of albuminuria or criteria for referral. Women were also less likely to undergo monitoring of creatinine or albuminuria, even among participants with diabetes (HR: 0.75; 0.74–0.76) or hypertension (HR: 0.76; 0.75–0.78). Multivariable adjustment including comorbidities, eGFR and indication for referral showed some attenuation of the effect, but a sex difference remained. Although in absolute terms there has been a gradual improvement in all nephrology care indicators over time, the observed sex gap persisted throughout. CONCLUSION: We found profound sex differences in the detection, recognition, monitoring and management (including referrals) of CKD in healthcare, also across high-risk groups and indications.